Pengaruh Pendidikan Kewirausahaan dan Literasi Digital terhadap Minat Kewirausahaan pada Mahasiswa Pendidikan Bisnis di Universitas Negeri Jakarta - Cindy Cindy; Corry Yohana; Nadya Fadillah Fidhyallah (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
This study examines the influence of entrepreneurship education and digital literacy on entrepreneurial interest among Business Education students at Universitas Negeri Jakarta. A quantitative approach with a survey method was employed, involving 197 students selected through quota sampling. Data were collected using a questionnaire with a 6-point Likert scale and analyzed using multiple linear regression. The results show that entrepreneurship education has a positive and significant partial effect on entrepreneurial interest (t = 4.973; p < 0.001). Digital literacy also has a positive and significant partial effect on entrepreneurial interest (t = 3.432; p < 0.001). Simultaneously, both variables significantly influence entrepreneurial interest (F = 121.296; p < 0.001). The Adjusted R² value of 0.551 indicates that both variables together explain 55.1% of the variation in entrepreneurial interest, while the remaining 44.9% is influenced by other factors outside the model. These findings confirm that entrepreneurship education and digital literacy are strategic factors that complement each other in fostering students' entrepreneurial interest in the digital era. This study contributes to the development of literature in entrepreneurship education and provides considerations for educational institutions in designing curricula that better support the development of students' entrepreneurial interest.